Experimental research of the geo-stress evolution law and effect in the intact coal and gas outburst process - Shang, Shaoyong; Zhang, Qinghua; Zhao, Yinghua; Diao, Yong; Yin, Jiakuan; Che, Yuheng; Kang, Xiaotong; Zhao, Bo (Frontiers in Earth Science, 2023)
Coal and gas outbursts are a potentially fatal hazard that must be managed when mining gassy coal seams. Mining-induced stress plays an important role in outbursts, while elastic potential is accumulated to provide energy for an outburst. In this study, a large-scale true triaxial (LSTT) apparatus was developed to conduct experiments and to understand the outburst mechanism and mining-induced geo-stress evolution law. In the LSTT experiments, coal and gas outbursts resulted from both stress and gas pressure and occurred in a limited balance area. Under the action of mining-induced stress, surrounding rock and coal are compressed. Thus, a large amount of elastic potential is accumulated to provide energy for a coal and gas outburst. Mining-induced stress promotes the development and expansion of the fracture in the coal body, which results in coal wall deformation and damage. The four types of coal wall instability are bodily movement of coal wall, layered separation of coal wall, collapse of coal wall, and break of coal wall. This study develops a classification scheme and management strategies for outbursts.